Accommodation Request Strategies Among Employees With Disabilities: Impacts and Associated Factors. (April 2020) - Dong, Shengli; Geyer, Paul; Hinton, Tameisha; Chin, Arizona
The purpose of this study is to examine the prevalence of different workplace accommodation request strategies, the effectiveness of different request approaches, and situational and individual factors associated with different request strategies for individuals with disabilities. Common action plans of accommodation requests may vary depending on decisions about mentioning the Americans With Disabilities Act (ADA) (or not) and whether a formal (or informal) request is submitted, though past literature has focused primarily on formal accommodation requests made under the auspices of the ADA. Participants ( n = 408) were recruited from rehabilitation agencies and organizations serving people with disabilities in the United States. The results indicated that informal requests without mentioning the ADA were found most often, followed by formal requests while not mentioning the ADA, formal requests while mentioning the ADA, and informal requests while mentioning the ADA. The odds of acquiring the requested accommodation were significantly higher, relative to other strategies, for requests made informally without mentioning the ADA. A variety of individual attributes capable of discerning when participants chose one strategy over another were observed; these included self-efficacy and outcome expectancy, negative affect, and an array of situational and personal attributes. Implications for research and practice were discussed.